GANGGUAN KESEHATAN MENTAL PADA PASCA PANDEMI - Ailiza Saroful Jannah (Jurnal Bimbingan Penyuluhan Islam, 2022)
This study aims to provide the effect of relaxation therapy and religious guidance counseling for people with mental health disorders. The method used in this research is descriptive qualitative with a case study approach. The results of the analysis showed that the behavior of mental health disorders such as stress, fear, excessive anxiety, can be treated through relaxation therapy and religious guidance counseling.